2014
DOI: 10.1007/s12155-014-9564-z
|View full text |Cite
|
Sign up to set email alerts
|

Humic Acid-Like and Fulvic Acid-Like Inhibition on the Hydrolysis of Cellulose and Tributyrin

Abstract: Enzymatic hydrolysis of complex wastes is a critical step for efficient biogas production in anaerobic digesters. Inhibition of this hydrolytic step was studied by addition of humic acid-like (HAL) and fulvic acid-like (FAL) substances, extracted from maize silage and fresh cow manure, to batch tests with cellulose and cellulases from Aspergillus niger and tributyrin and lipases from Candida rugosa. To confirm the inhibition results, microbially catalysed hydrolysis trials were performed, where Fibrobacter suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 23 publications
3
45
1
Order By: Relevance
“…Humic acid (HA) is a product of the decay and/or polymerisation of organic matter and behaves like a weak acid polyelectrolyte (Veeken and Hamelers, 1999). Previous studies have reported possible inhibition by humic substances within the concentration range 0.5 to 5.0 g L-1 (Fernandes et al, 2014;Ghasimi et al, 2016).…”
Section: Inhibitionmentioning
confidence: 97%
See 4 more Smart Citations
“…Humic acid (HA) is a product of the decay and/or polymerisation of organic matter and behaves like a weak acid polyelectrolyte (Veeken and Hamelers, 1999). Previous studies have reported possible inhibition by humic substances within the concentration range 0.5 to 5.0 g L-1 (Fernandes et al, 2014;Ghasimi et al, 2016).…”
Section: Inhibitionmentioning
confidence: 97%
“…For example, a manure digester was known to be inhibited by ammonia (Yenigun et al 2013) and/or humic acid (HA) (Brons et al, 1985;Fernandes et al, 2014), which is considered highly relevant for solid manure residues. Yet relevant studies have largely focused on the inhibitory effect of ammonia (Yenigun et al 2013) with much less attention given to HA (Brons et al, 1985;Fernandes et al, 2014). This is despite the observations of previous works that suggested that HA could inhibit substrate solubilisation (Brons et al, 1985;Fernandes et al, 2014).…”
Section: Research Motivationmentioning
confidence: 99%
See 3 more Smart Citations